Method for calculating the use of nozzle hydrodiodes in design of two-tube hydraulic shock absorber - S. Yu. Kaigorodov; A. A. Shaposhkov; I. V. Tsvetkov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The development of a method for calculating the use of nozzle hydrodiodes in the design of a two-tube hydraulic shock absorber is carried out by considering such problems as the fragility and wear of movable elements (valves) in the design of a hydraulic shock absorber. The paper considers a method of calculation of the shock absorber with hydrododone (the fixed elements). The scientific novelty and task is to replace the movable hydraulic valves in the shock absorber design with nozzle hydraulic diodes, which, theoretically, will extend the service life of this unit, due to the lack of movement dynamics and wear of moving parts